Anton Pannekoek’s Epistemic Virtues in Astronomy and Socialism: Personae and the Practice of Science - Tai, Chaokang; van Dongen, Jeroen (BMGN - Low Countries Historical Review, 2016)
Anton Pannekoek (1873-1960) was both an innovative astronomer and an influential Marxist. In this article we will investigate both his Milky Way research and Marxist philosophy, with special focus on his ideal scholarly persona and the epistemic virtues he advocated in his research. This focus allows us to place Pannekoek in the larger development of science methodology during the nineteenth and early twentieth century and, most importantly, offers insight into how Pannekoek’s scientific and socialist research were related. This article is part of the special issue ’Scholarly Personae’. Anton Pannekoek en zijn epistemische deugden in astronomie en socialisme. Personae in de praktijk Anton Pannekoek (1873-1960) was zowel innovatief astronoom als invloedrijk marxist. Dit artikel bespreekt zijn onderzoek naar de structuur van de Melkweg en zijn marxistische filosofie, waarbij we in het bijzonder onze aandacht richten op Pannekoeks epistemische deugden en de daarmee geassocieerde ideale personae. Dit perspectief stelt ons in staat om Pannekoek in de bredere ontwikkeling van de wetenschappelijke methodologie van de negentiende en vroege twintigste eeuw te plaatsen. Voorts biedt het ons inzicht in hoe Pannekoeks sterrenkundige en socialistische onderzoek gerelateerd waren. Dit artikel maakt deel uit van het themanummer ’Scholarly Personae’.